A Comprehensive and Critical Review on Analytical and Bioanalytical methods for Metformin Hydrochloride, Dapagliflozin, and Saxagliptin - Desai, Saloni; Maradia, Rajnikant B.; Suhagia, Bhanubhai N (Current Pharmaceutical Analysis, 2023)
A new antidiabetic drug combination of Metformin Hydrochloride, Dapagliflozin, and Saxagliptin have been recently approved for type II diabetes. This is marketed by Takeda Pharmaceuticals under the brand name Qternmet XR. Although different analytical and bioanalytical methods using different techniques such as liquid chromatography, high-performance liquid chromatography, high-performance thin-layer chromatography, gas chromatography, spectrophotometry, spectrofluorimetric methods coupled with ultraviolet, fluorescence, mass, or tandemmass spectrometry detection have already been developed for the determination of Metformin Hydrochloride, Dapagliflozin, and Saxagliptin. Sensitive, cost-effective, and more optimized methods are yet required. Therefore, this review summarizes the main analytical and bioanalytical aspects regarding not only simultaneous estimation but also stability-indicating methods, kinetic studies, and impurity analysis for the analysis of proposed drugs in bulk and pharmaceutical dosage forms. Thus, this review gathers, for the first time, important background information on all analytical and bioanalytical methods that have been developed and applied for the determination of Metformin Hydrochloride, Dapagliflozin, and Saxagliptin, which should be considered as a starting point if new techniques are aimed to be implemented for these drugs.
Keywords: bioanalytical method